Influence of Vascular Access Type on Sex and Ethnicity-Related Mortality in Hemodialysis-Dependent Patients - Woo, Karen (The Permanente Journal, 2012)
Objectives: To determine whether sex- and ethnicity-based mortality differences in patients dependent on hemodialysis (hemodialysis patients) are because of prevalence of vascular access type. Methods: Southern California Permanente Medical Group Renal Database, which contained 5821 chronic hemodialysis patients between 2000 and 2008, was studied. Results: Mean age of the patients was 62 years, and 59% were male. Of the population, 33% were white; 32%, Hispanic; 23%, African American; 9%, Asian/Pacific Islander; and 3%, other race or ethnicity. Predominant access type over the course of the study was arteriovenous fistula (AVF) in 73%, arteriovenous graft (AVG) in 12%, and tunneled catheter in 14%. There was a higher percentage of AVF in whites (71%) than in African Americans (63%). Risk of death was independently increased by age (hazard ratio [HR], 1.04; 95% confidence interval [CI], 1.04–1.05), male sex (HR, 1.33; 95% CI, 1.22–1.45), diabetes (HR, 1.22; 95% CI, 1.12–1.33), use of an AVG (HR, 1.51; 95% CI, 1.34–1.71) or a tunneled catheter (HR, 6.45; 95% CI, 5.78–7.20). Compared with whites, African-American race decreased the risk of death (HR, 0.63; 95% CI, 0.56–0.70), as did Asian/Pacific Islander (HR, 0.58; 95% CI, 0.49–0.69), Hispanic (HR, 0.58; 95% CI, 0.51–0.65), and other race (HR, 0.67; 95% CI, 0.52–0.86). Conclusion: Age, sex, race or ethnicity, access type, and diabetes are independent risk factors for mortality in hemodialysis patients. After controlling for potential confounders, when compared with whites, minorities all demonstrate significantly decreased risk of mortality. African Americans had reduced mortality risk despite a lower prevalence of arteriovenous fistula compared with whites. Male sex increased mortality. Differences in mortality between sexes and ethnicities in this population cannot be accounted for by differences in type of dialysis access.